Metabolic Niches and Biodiversity: A Test Case in the Deep Sea Benthos - McClain, Craig R.; Webb, Thomas J.; Nunnally, Clifton C.; Dixon, S. River; Finnegan, Seth; Nelson, James A. (Frontiers in Marine Science, 2020)
The great anthropogenic alterations occurring to carbon availability in the oceans necessitates an understanding of the energy requirements of species and how changes in energy availability may impact biodiversity. The deep oceans are characterized naturally by extremely low availability of chemical energy and are particularly vulnerable to changes in carbon flux from surface waters. Because the energetic requirements of an organism impact nearly every aspect of their ecology and evolution, we hypothesize that species are adapted to specific levels of carbon availability and occupy a particular metabolic niche. We test this hypothesis in deep-sea invertebrates specifically examining how energetic demand, axes of the metabolic niche, and geographic range size vary over gradients of chemical energy availability. We find that species with higher energetic expenditures, and ecologies associated with high energy demand, are located in areas with higher chemical energy availability. In addition, we find that range size and location of deep-sea species is determined by geographic patterns in chemical energy availability. Our findings indicate that deep-sea species are adapted to specific energy regimes, the metabolic niche can potentially link scales from individuals to ecosystems, and link adaptation to patterns in biogeography and biodiversity.